Coinfection with Leishmania infantum and Toxoplasma gondii in Domestic Cats from a Region with a High Prevalence of Feline Immunodeficiency Virus - Bezerra, José Artur Brilhante; Haisi, Amanda [UNESP]; Rocha, Gabrielle dos Santos [UNESP]; Lima, Suellen Gonçalves [UNESP]; Brasil, Arthur Willian de Lima; Tomaz, Klívio Loreno Raulino; Fornazari, Felipe [UNESP]; Langoni, Helio [UNESP]; Araújo Junior, João Pessoa [UNESP]; Antunes, João Marcelo Azevedo de Paula; Azevedo, Sérgio Santos de (MDPI, 2024)
The aim of this study was to investigate the coinfection of feline retroviruses (feline immunodeficiency virus—FIV, and the feline leukemia virus—FeLV) with Leishmania infantum and Toxoplasma gondii and the factors associated with these pathogens in domestic cats from Mossoró, a city endemic for canine and human leishmaniasis situated in the semiarid region of Northeast Brazil. Blood samples from 120 cats were collected, and an epidemiological questionnaire was applied to investigate the risk factors associated with the infections. Retroviruses, L. infantum, and T. gondii infections were assessed using a point-of-care ELISA and quantitative PCR (qPCR), indirect fluorescent antibody test (IFAT) and qPCR, and IFAT, respectively. The overall seroprevalences observed were 35% (95% CI = 27.0–43.8%) for FIV, 0.8% (95% CI = 0.1–4.5%) for FeLV, 25.8% (95% CI = 18.8–34.3%) for T. gondii, and 4.2% (95% CI = 1.7–9.3%) for L. infantum. Coinfection with FIV and L. infantum was observed in 2.5% (3/120) of the assessed cats, while 12.5% (15/120) were coinfected with FIV and T. gondii. No significant association was found among the investigated agents (p > 0.05). The factors associated with FIV infection in the multivariable analysis were male sex and age above 78 months. The findings of this study demonstrated a high rate of FIV infection in cats from the Brazilian semiarid region and the exposure of these animals to zoonotic and opportunistic agents. Due to the immunosuppressive potential of FIV, cats infected with this retrovirus should be screened for coinfections with L. infantum and T. gondii, and preventative measures should be adopted.
Keywords: epidemiology; feline leishmaniasis; Felis catus; FeLV; FIV; toxoplasmosis